Catfish (Clarias sp.) as an animal protein source to improve serum albumin levels of hemodialysis patients - Widiany, Fery Lusviana; Astuti, Ari Tri (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2021)
Background: Hemodialysis patients often experience hypoalbuminemia complications, which occur mainly due to decreased synthesis due to inflammation, lack of protein intake, the fluid status of patients, and losses from the dialysate. Another problem in hemodialysis is malnutrition, with a prevalence between 23â€“73% globally. Gastrointestinal disorders such as nausea, vomiting, and decreased appetite also often occur in hemodialysis. Therefore, hemodialysis patients need to get nutritional support, which can be given in the form of catfish abon, one of the local Indonesian food.Objective: To determine the effectiveness of the use of catfish as a source of animal protein to improve the albumin levels of hemodialysis patients.Materials and Methods: This was a quasi-experimental study with a pre-post test design. This study involved 34 hemodialysis patients as subjects, with inclusion criteria, were routinely two times a week, aged >18 years, willing to be the subject and follow the research procedures, have albumin levels â‰¥3.0 g/dL, and no catfish allergies. Patients with anasarca edema, experiencing complications of diabetes mellitus and malignancy were excluded. The dependent variable was albumin content, while the independent variable was catfish as an animal protein source. Data were analyzed univariate and bivariate by Fisher's Exact test.Results: Fisher's Exact test results on the effectiveness of using catfish as an animal protein source to improve albumin levels of hemodialysis patients showed p-value=0.048.Conclusion: The use of catfish as an effective animal protein source significantly affected on improving albumin levels in hemodialysis patients.